Self-adhesive SBS modified asphalt waterproof coiled material
By adopting a gradient tire-based design and block copolymer interface layer in the modified asphalt waterproof roll, combined with an optimized low-modulus bitumen coating and UV-resistant and anti-bacterial coating, the problems of insufficient mechanical properties of the roll and low bond strength in high temperature environments are solved, and higher durability, stability and construction adaptability are achieved.
Patent Information
- Application Number
- CN202411753047.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
The existing modified asphalt waterproof coils have shortcomings in mechanical properties and structural design, and it is difficult to meet the stress requirements of the coils at different parts at the same time. The bonding strength is easily affected under high temperature environments, and the layers are aging and detached after long-term use.
Self-adhesive SBS modified asphalt waterproof coil is used to improve tensile strength and ductility through gradient tire base design and block copolymer interface layer; optimized low-modulus asphalt coatings are used in low temperature environments to enhance initial adhesive performance; and anti-ultraviolet and antibacterial coatings are applied to the surface to delay aging and inhibit mold growth.
It significantly improves the tensile strength, tear strength and ductility of the coil material, enhances interlayer binding force and low-temperature construction adaptability, delays aging and inhibits mold growth, and improves overall durability and stability.
Smart Images

Figure CN119571639A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof coiled materials, in particular to a self-adhesive SBS modified asphalt waterproof coiled material. Background Art
[0002] The base layer of modified asphalt waterproofing membrane is the key part that determines its mechanical properties. It plays an important role in the tensile strength, dimensional stability and durability of the membrane. The common base materials on the market currently include polyester fiber and glass fiber. These materials have certain advantages in specific environments, but because they are mostly designed with a single homogeneous structure, it is difficult to simultaneously meet the force requirements of the membrane in different parts.
[0003] To address this problem, some traditional solutions have tried to improve the overall strength of the base material or increase its thickness to make up for the deficiency. However, this method increases the rigidity of the material, reduces the ductility and construction adaptability of the coil, and is more likely to cause cracks in an environment with a large temperature difference. In addition, the homogeneous base structure lacks specificity in dealing with uneven stress, which affects the overall service life.
[0004] In addition, some modified asphalt waterproofing membranes adopt a single-layer or stacked structure. For example, self-adhesive membranes are suitable for low-temperature construction, but the bonding strength is easily affected in high-temperature environments. Although hot-melt membranes are adaptable to high temperatures, their construction is more complicated and have higher requirements for the base layer. The interlayer bonding strength of double-layer membranes is insufficient, and after long-term use, the interlayers will age and detach. Therefore, a self-adhesive SBS modified asphalt waterproofing membrane is urgently needed to solve such problems. Summary of the invention
[0005] In view of the above existing problems, the present invention is proposed.
[0006] The invention provides a self-adhesive SBS modified asphalt waterproofing membrane to solve the problems that the current waterproofing membrane has deficiencies in mechanical properties and structural design.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0008] The embodiment of the present invention provides a self-adhesive SBS modified asphalt waterproofing membrane, the composition ratio of which includes:
[0009] Asphalt matrix 50%-70%, SBS modifier 7%-10%, C9 petroleum resin tackifier 1%-3%, coumarone resin toughener 1%-2%, polyester fiber PET 8%-12%, polypropylene fiber PP 3%-5%, glass fiber GF 1%-2%, high molecular polyethylene fiber UHMWPE 4%-6%, dihydroxybenzophenone UV-531 0.5%-1%, acrylic emulsion 2%-3% and isothiazolinone OIT 0.1%-1%;
[0010] The SBS modifier includes SBS in high modulus and low modulus modified asphalt.
[0011] As a preferred embodiment of the self-adhesive SBS modified asphalt waterproofing membrane of the present invention, the preparation method of the self-adhesive SBS modified asphalt waterproofing membrane is as follows:
[0012] Step S1, preparation of gradient base.
[0013] A gradient tire base is prepared, wherein the gradient tire base includes a center layer, an intermediate layer and an outer tire base.
[0014] Step S2, block copolymer interface layer,
[0015] The grafted SBS containing acrylic acid grafting is mixed with C9 petroleum resin tackifier in a melt mixing device, melt mixed at a temperature of 150-180°C, and after uniform mixing, a transition layer coating liquid is formed, and the block copolymer coating liquid is sprayed on both sides of the intermediate layer tire base to form a block copolymer interface layer, and the coating thickness is 0.2-0.5mm. The coating is carried out by a double-head roller coating machine, and the coating temperature is 180°C and the coating pressure is 10MPa;
[0016] Step S3, asphalt coating,
[0017] Asphalt coating is carried out using a precision coating machine equipped with heating, pressure control and multi-point coating head. The coating speed is set at 0.5-1.0m / min. Asphalt coating includes the first coating and the second coating.
[0018] Step S4, surface anti-ultraviolet and antibacterial coating,
[0019] Dihydroxybenzophenone UV-531 and acrylic emulsion were mixed in a ratio of 2:98 to prepare an anti-ultraviolet coating, and a 1% concentration of isothiazolinone solution was used as an antibacterial coating for anti-ultraviolet and antibacterial coating.
[0020] As a preferred solution of the self-adhesive SBS modified asphalt waterproofing membrane described in the present invention, the preparation process of the center layer is as follows:
[0021] The polyethylene terephthalate (PET) particles are drawn into fiber filaments at a temperature of 280-300°C using a melt spinning device, the fiber diameter is controlled at 15-25 μm, the fiber filaments are cross-woven using a knitting machine or an interweaving machine, the weaving density is 10-12 wefts / cm, the porosity is maintained at 20%-30%, and the center layer tire base is formed in a heat setting machine at a temperature of 180-220°C for 3-5 minutes.
[0022] The intermediate layer preparation process:
[0023] The fiber dispersing equipment is used to evenly mix the polypropylene fiber PP and the glass fiber GF in a ratio of 7:3. The mixed fibers are put into the hot rolling mill and hot rolled at a temperature of 150-180°C and a pressure of 10-15MPa to form a thin sheet-like intermediate layer tire base.
[0024] The outer layer preparation process:
[0025] The high molecular polyethylene fiber UHMWPE is processed by gel spinning process. The fiber diameter after processing is maintained at 8-12μm. The processed high molecular polyethylene fiber is laid in layers with a layer thickness of 0.5-1mm. Then, a hot pressing molding process is adopted to perform hot pressing at a temperature of 120°C and a pressure of 5-10MPa to form an outer tire base.
[0026] As a preferred embodiment of the self-adhesive SBS modified asphalt waterproofing membrane of the present invention, wherein: in the step S2, the grafted SBS and the C9 petroleum resin tackifier are mixed to form a mixture, wherein the grafted SBS accounts for 85%-90% of the mixture, and the C9 petroleum resin tackifier accounts for 10%-15% of the mixture;
[0027] The function of the grafted modified SBS interface layer is to enhance the interlayer bonding force. It is located between the asphalt coating area of the center layer and the low modulus asphalt coating area of the outer tire base. Through the chemical bonding force of the block copolymer, the long-term stability of different layers of the tire base and the asphalt coating is ensured.
[0028] As a preferred embodiment of the self-adhesive SBS modified asphalt waterproofing membrane of the present invention, the first coating is:
[0029] The high modulus SBS modified asphalt is heated to 180-200℃, the center layer base is transported into the coating area of the coater, and the asphalt is evenly applied from the multi-point coating head. The coating thickness is controlled at 2-3mm and combined by roller pressing.
[0030] As a preferred embodiment of the self-adhesive SBS modified asphalt waterproofing membrane of the present invention, the second coating is:
[0031] The low modulus SBS modified asphalt is heated to 160-180℃, the outer layer of the tire is transported into the coating area of the coater, and the asphalt is evenly applied from the multi-point coating head. The coating thickness is controlled at 2-3mm, and the coil is made by rolling. The two coatings are respectively for the center layer and the outer layer of the tire, and the two are carried out independently. The mechanical properties of the center layer of the tire are enhanced by the first coating, and the flexibility and bonding properties of the outer layer of the tire are enhanced by the second coating.
[0032] As a preferred embodiment of the self-adhesive SBS modified asphalt waterproofing membrane described in the present invention, in the step S3, the interface layer is cured by high-temperature rolling when the asphalt is coated, and both sides of the middle layer have a cured block copolymer interface layer, which is then combined with the asphalt coating; the asphalt coating and the middle layer are firmly bonded by the chemical bonding force of the block copolymer.
[0033] As a preferred embodiment of the self-adhesive SBS modified asphalt waterproofing membrane described in the present invention, the high modulus SBS modified asphalt ratio is:
[0034] Asphalt matrix 80%-85%, SBS modifier 10%-14% and tackifier 3%-5%,
[0035] Low modulus SBS modified asphalt ratio:
[0036] Asphalt matrix 85%-90%, SBS modifier 5%-8%, toughening agent coumarone resin, 3%-5%.
[0037] As a preferred embodiment of the self-adhesive SBS modified asphalt waterproofing membrane described in the present invention, the method of performing anti-ultraviolet and antibacterial coating is as follows:
[0038] An automatic sprayer is used to spray anti-ultraviolet coating on the outer surface of the roll at a spraying pressure of 0.3-0.5MPa with a spraying thickness of 30-50μm. After the anti-ultraviolet layer is naturally air-dried for 15-20 minutes, antibacterial coating is sprayed with a spraying thickness of 40-60μm to form a surface protection layer to obtain a self-adhesive SBS modified asphalt waterproof roll.
[0039] As a preferred embodiment of the self-adhesive SBS modified asphalt waterproofing membrane of the present invention, the structural order of the waterproofing membrane is as follows:
[0040] Center layer base,
[0041] High modulus bituminous coating,
[0042] Block copolymer interfacial layer,
[0043] The middle layer of the tire base,
[0044] Block copolymer interfacial layer,
[0045] Low modulus bituminous coating,
[0046] Outer tire base,
[0047] UV resistant and antibacterial surface coating.
[0048] The beneficial effects of the present invention are:
[0049] The self-adhesive SBS modified asphalt waterproof membrane provided by the present invention adopts a gradient base design, which improves the tensile strength, tear strength and ductility, and solves the problem of insufficient mechanical properties of the traditional base; the block copolymer interface layer significantly enhances the interlayer bonding force and effectively prevents stratification; the anti-ultraviolet coating and the antibacterial coating delay aging and inhibit mold growth, thereby improving environmental adaptability; the optimized low modulus asphalt coating enhances the initial adhesion performance at low temperatures, meets the requirements of low-temperature construction, and has better durability, stability and construction adaptability. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0051] Figure 1 This is a flow chart for preparing a self-adhesive SBS modified asphalt waterproof membrane in Example 1. DETAILED DESCRIPTION
[0052] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.
[0053] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0054] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0055] Example 1, reference Figure 1 , which is the first embodiment of the present invention, and provides a self-adhesive SBS modified asphalt waterproofing membrane, the composition ratio includes:
[0056] Asphalt matrix 63.00%, SBS modifier 9.00%, C9 petroleum resin tackifier 3.00%, coumarone resin toughener 1.00%, polyester fiber 10.00%, polypropylene fiber 5.00%, glass fiber 2.00%, high molecular polyethylene fiber 4.00%, dihydroxybenzophenone 0.50%, acrylic emulsion 2.00% and isothiazolinone 0.50%,
[0057] The coil preparation steps include:
[0058] Step S1, preparation of gradient base.
[0059] A gradient tire base is prepared, wherein the gradient tire base includes a center layer, an intermediate layer and an outer tire base.
[0060] Center layer preparation process:
[0061] The polyethylene terephthalate (PET) particles are drawn into fiber filaments at a temperature of 300°C using a melt spinning device, the fiber diameter is controlled to be 20 μm, the fiber filaments are cross-woven using a knitting machine or an interweaving machine, the weaving density is 10-12 wefts / cm, the porosity is maintained at 30%, and the center layer tire base is formed in a heat setting machine at a temperature of 220°C for 5 minutes.
[0062] Intermediate layer preparation process:
[0063] The fiber dispersing equipment is used to evenly mix the polypropylene fiber PP and the glass fiber GF in a ratio of 7:3. The mixed fibers are put into a hot rolling mill and hot rolled at a temperature of 180°C and a pressure of 15MPa to form a thin sheet-like intermediate layer tire base.
[0064] Outer layer preparation process:
[0065] The high molecular polyethylene fiber UHMWPE is processed by gel spinning process, and the processed fiber diameter is 8-12μm. The processed high molecular polyethylene fiber is laid in a stacking manner with a stacking thickness of 0.5mm, and then hot-pressed at a temperature of 120°C and a pressure of 10MPa to form an outer tire base;
[0066] Step S2, block copolymer interface layer,
[0067] The grafted SBS containing acrylic acid grafting is mixed with C9 petroleum resin tackifier in a melt mixing device, melt mixed at a temperature of 180°C, and mixed evenly to form a transition layer coating liquid, and the block copolymer coating liquid is sprayed on both sides of the intermediate layer tire base to form a block copolymer interface layer, the coating thickness is 0.5mm, and the coating is carried out by a double-head roller coating machine, the coating temperature is 180°C, and the coating pressure is 10MPa;
[0068] In step S2, the grafted SBS and the C9 petroleum resin tackifier are mixed to form a mixture, wherein the grafted SBS accounts for 90% of the mixture and the C9 petroleum resin tackifier accounts for 10% of the mixture;
[0069] The function of the grafted modified SBS interface layer is to enhance the interlayer bonding force. It is located between the asphalt coating area of the center layer and the low modulus asphalt coating area of the outer tire base. Through the chemical bonding force of the block copolymer, the long-term stability of different layers of the tire base and the asphalt coating is ensured.
[0070] Step S3, asphalt coating,
[0071] Asphalt coating is carried out using a precision coating machine equipped with heating, pressure control and a multi-point coating head. The coating speed is set at 1.0m / min. The asphalt coating includes the first coating and the second coating.
[0072] First coat:
[0073] The high modulus SBS modified asphalt is heated to 200℃, the center layer tire base is transported into the coating area of the coating machine, and the asphalt is evenly applied from the multi-point coating head with a coating thickness of 3mm, and combined by roller pressing.
[0074] Second coat:
[0075] The low modulus SBS modified asphalt is heated to 180°C, the outer layer of the tire base is transported into the coating area of the coating machine, and the asphalt is evenly applied from the multi-point coating head with a coating thickness of 3mm, and the coil is obtained by rolling and bonding;
[0076] The two coatings are applied to the center layer and the outer tire base respectively, and the two are carried out independently. The center tire base is enhanced in mechanical properties by the first coating, and the outer tire base is enhanced in flexibility and bonding properties by the second coating.
[0077] In step S3, the interface layer is cured by high-temperature rolling when the asphalt is applied, and both sides of the middle layer have a cured block copolymer interface layer, which is then combined with the asphalt coating; the asphalt coating and the middle layer are firmly bonded by the chemical bonding force of the block copolymer;
[0078] High modulus SBS modified asphalt ratio:
[0079] Asphalt base 85%, SBS modifier 10% and tackifier 5%,
[0080] Low modulus SBS modified asphalt ratio:
[0081] Asphalt matrix 90%, SBS modifier 6%, toughening agent coumarone resin, 4%;
[0082] Step S4, surface anti-ultraviolet and antibacterial coating,
[0083] The anti-ultraviolet coating is prepared by mixing dihydroxybenzophenone UV-531 and acrylic emulsion in a ratio of 2:98, and a 1% concentration of isothiazolinone solution is used as an antibacterial coating for anti-ultraviolet and antibacterial coating;
[0084] The method of carrying out anti-ultraviolet and antibacterial coating is:
[0085] An automatic sprayer is used to spray an anti-ultraviolet coating on the outer surface of the roll at a spraying pressure of 0.5 MPa, with a spraying thickness of 50 μm. After the anti-ultraviolet layer is naturally air-dried for 20 minutes, an antibacterial coating is sprayed with a spraying thickness of 50 μm to form a surface protection layer, thereby obtaining a self-adhesive SBS modified asphalt waterproof roll;
[0086] Example 2
[0087] The difference from Example 1 is that the ingredients are asphalt matrix 69.00%, SBS modifier 7.00%, C9 petroleum resin tackifier 1.50%, coumarone resin toughening agent 2.00%, polyester fiber 8.50%, polypropylene fiber 3.50%, glass fiber 1.50%, high molecular polyethylene fiber 4.00%, dihydroxybenzophenone 0.50%, acrylic emulsion 2.00% and isothiazolinone 0.50%;
[0088] and the temperature of the two asphalt coatings in the asphalt coating is set to 180°C;
[0089] Example 3
[0090] The difference from Example 1 is that the ingredients are asphalt matrix 69.00%, SBS modifier 7.00%, C9 petroleum resin tackifier 1.50%, coumarone resin toughening agent 2.00%, polyester fiber 8.50%, polypropylene fiber 3.50%, glass fiber 1.50%, high molecular polyethylene fiber 4.00%, dihydroxybenzophenone 0.50%, acrylic emulsion 2.00% and isothiazolinone 0.50%,
[0091] Experimental example
[0092] Tire base samples were prepared according to the preparation methods of Examples 1-3 and Publication No. CN110746930A, respectively, and prepared with reference to Examples 1 and 3 of the preparation method thereof, as control group 1 and control group 2; in the preparation materials of this scheme: asphalt matrix was purchased from Foshan Nanhai Lianyun Road Maintenance Engineering Co., Ltd., SBS modifier was purchased from Borida (Dongguan) New Materials Co., Ltd., C9 petroleum resin tackifier was purchased from Jinan Xinhou Trading Co., Ltd., coumarone resin toughener was purchased from Guangzhou Shuangli Rubber Raw Materials Trading Co., Ltd., dihydroxybenzophenone was purchased from Shandong Ranhang Biotechnology Co., Ltd., acrylic emulsion was purchased from Shandong Junda Chemical Co., Ltd., isothiazolinone was purchased from Jinan Luying Chemical Co., Ltd., and fiber materials were all purchased from Dongguan Jinyuan Composite Materials Co., Ltd.;
[0093] Experiment 1: Evaluation of the mechanical properties of the gradient tire base
[0094] Tensile strength: According to GB / T 328.9 standard, the tensile strength is measured using a universal material testing machine.
[0095] Tear strength: According to GB / T 529 standard, the tear resistance of the middle layer is measured.
[0096] Ductility: According to GB / T 328.10 standard, the maximum elongation of the sample is measured;
[0097] Experiment 2: Evaluation of interlayer bond strength
[0098] Take a 5×10 cm coil sample, where the interlayer contains a block copolymer interface layer,
[0099] According to GB / T 328.13 standard, the peel strength between the interface layer and the asphalt coating was measured using a 90° peel tester.
[0100] After aging the sample at 80°C for 14 days, the test was repeated to observe the change in peel strength.
[0101] Whether the peel strength is significantly higher than that of traditional coiled materials, and whether it exhibits excellent anti-aging interlayer adhesion;
[0102] Experiment 3: Verification of anti-ultraviolet and antibacterial properties
[0103] The samples were exposed to UV-A light (UV irradiation intensity 0.76 W / m 2 , wavelength 340nm), irradiation time is 1000 hours,
[0104] According to GB / T 14522 standard, the tensile strength and mass loss rate before and after aging were measured, and the anti-ultraviolet performance was evaluated.
[0105] Inoculate common molds (such as Penicillium and Aspergillus niger) on the coating surface, conduct mold exposure test according to GB / T 21866 standard, and observe the colony growth after 14 days;
[0106] Experiment 4: Verification of low temperature construction adaptability
[0107] The samples were placed in a low temperature environment (-10°C) for 12 hours and then taken out.
[0108] According to GB / T 4851 standard, the rolling ball initial adhesion test method is used to evaluate the bonding performance of the self-adhesive layer in a low temperature environment.
[0109] The initial peel strength at low temperature was measured using a peel strength tester;
[0110] The gradient fetal base samples of this scheme (Example 1, Example 2, Example 3) were tested respectively and compared with the above-mentioned fetal base samples (Control Group 1, Control Group 2);
[0111] Data comparison table 1
[0112]
[0113] Data comparison table 2
[0114]
[0115] Combining Table 1 and Table 2, we can see that:
[0116] The tensile strength of the gradient tire base samples in this scheme is 9.48-9.65MPa, and the tear strength is 83.27-84.12kN / m, which are significantly higher than the 7.75-7.92MPa and 56.45-57.18kN / m of the traditional homogeneous tire base samples. The structural optimization of the gradient tire base significantly enhances the overall mechanical properties and demonstrates superiority in tear strength.
[0117] The ductility of this solution is 115.86%-117.42%, which is significantly better than the 91.64%-93.21% of the traditional tire base samples, indicating that the gradient tire base has better adaptability under complex stress environments; in the initial interlayer peeling strength, this solution is 5.73-5.88N / cm, which is significantly higher than the 3.59-3.71N / cm of the traditional samples; after aging, the interlayer peeling strength of this solution only decreases by about 4%-5% (to 5.47-5.61N / cm), while the traditional sample decreases by about 20%-22% (to 2.85-2.96N / cm);
[0118] The mass loss rate of this solution is 3.21%-3.34%, which is much lower than the 9.58%-9.71% of the traditional samples, indicating that the anti-UV coating effectively delays aging; the inhibition rate of this solution is 90.87%-91.36%, which is significantly higher than the 45.73%-46.18% of the traditional samples, indicating that the antibacterial coating has a significant improvement in the antibacterial effect;
[0119] The low-temperature initial adhesion strength of this solution is 2.18-2.25N / cm, which is much higher than the 0.92-0.97N / cm of the traditional sample, indicating that the self-adhesive layer can still maintain good adhesion performance in a low-temperature environment and is more suitable for low-temperature construction.
[0120] In summary, the experimental data show that the gradient base waterproof membrane of this scheme significantly improves the mechanical properties, interlayer adhesion, aging resistance and adaptability to low-temperature construction, and has practical promotion value.
[0121] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A self-adhesive SBS modified asphalt waterproofing membrane, characterized in that: The ingredients include: Asphalt matrix 50%-70%, SBS modifier 7%-10%, C9 petroleum resin tackifier 1%-3%, coumarone resin toughener 1%-2%, polyester fiber PET 8%-12%, polypropylene fiber PP 3%-5%, glass fiber GF 1%-2%, high molecular polyethylene fiber UHMWPE 4%-6%, dihydroxybenzophenone UV-531 0.5%-1%, acrylic emulsion 2%-3% and isothiazolinone OIT 0.1%-1%; The SBS modifier includes SBS in high modulus and low modulus modified asphalt.
2. A self-adhesive SBS modified asphalt waterproofing membrane as claimed in claim 1, characterized in that: The preparation method of the self-adhesive SBS modified asphalt waterproofing membrane is as follows: Step S1, preparation of gradient base. A gradient tire base is prepared, wherein the gradient tire base includes a center layer, an intermediate layer and an outer tire base. Step S2, block copolymer interface layer, The grafted SBS containing acrylic acid grafting is mixed with C9 petroleum resin tackifier in a melt mixing device, melt mixed at a temperature of 150-180°C, and after uniform mixing, a transition layer coating liquid is formed, and the block copolymer coating liquid is sprayed on both sides of the intermediate layer tire base to form a block copolymer interface layer, and the coating thickness is 0.2-0.5mm. The coating is carried out by a double-head roller coating machine, and the coating temperature is 180°C and the coating pressure is 10MPa; Step S3, asphalt coating, Asphalt coating is carried out using a precision coating machine equipped with heating, pressure control and multi-point coating head. The coating speed is set at 0.5-1.0m / min. Asphalt coating includes the first coating and the second coating. Step S4, surface anti-ultraviolet and antibacterial coating, Dihydroxybenzophenone UV-531 and acrylic emulsion were mixed in a ratio of 2:98 to prepare an anti-ultraviolet coating, and a 1% concentration of isothiazolinone solution was used as an antibacterial coating for anti-ultraviolet and antibacterial coating.
3. A self-adhesive SBS modified asphalt waterproofing membrane as claimed in claim 2, characterized in that: The central layer preparation process: The polyethylene terephthalate (PET) particles are drawn into fiber filaments at a temperature of 280-300°C using a melt spinning device, the fiber diameter is controlled at 15-25 μm, the fiber filaments are cross-woven using a knitting machine or an interweaving machine, the weaving density is 10-12 wefts / cm, the porosity is maintained at 20%-30%, and the center layer tire base is formed in a heat setting machine at a temperature of 180-220°C for 3-5 minutes. The intermediate layer preparation process: The fiber dispersing equipment is used to evenly mix the polypropylene fiber PP and the glass fiber GF in a ratio of 7:
3. The mixed fibers are put into the hot rolling mill and hot rolled at a temperature of 150-180°C and a pressure of 10-15MPa to form a thin sheet-like intermediate layer tire base. The outer layer preparation process: The high molecular polyethylene fiber UHMWPE is processed by gel spinning process. The fiber diameter after processing is maintained at 8-12μm. The processed high molecular polyethylene fiber is laid in layers with a layer thickness of 0.5-1mm. Then, a hot pressing molding process is adopted to perform hot pressing at a temperature of 120°C and a pressure of 5-10MPa to form an outer tire base.
4. A self-adhesive SBS modified asphalt waterproofing membrane as claimed in claim 3, characterized in that: In the step S2, the grafted SBS and the C9 petroleum resin tackifier are mixed to form a mixture, wherein the grafted SBS accounts for 85%-90% of the mixture, and the C9 petroleum resin tackifier accounts for 10%-15% of the mixture.
5. A self-adhesive SBS modified asphalt waterproofing membrane as claimed in claim 4, characterized in that: The first coat: The high modulus SBS modified asphalt is heated to 180-200℃, the center layer base is transported into the coating area of the coater, and the asphalt is evenly applied from the multi-point coating head. The coating thickness is controlled at 2-3mm and combined by roller pressing.
6. A self-adhesive SBS modified asphalt waterproofing membrane as claimed in claim 5, characterized in that: The second coating: The low modulus SBS modified asphalt is heated to 160-180°C, the outer layer of the base is transported into the coating area of the coater, and the asphalt is evenly applied from the multi-point coating head. The coating thickness is controlled at 2-3mm, and the coil is made by rolling and combining.
7. A self-adhesive SBS modified asphalt waterproofing membrane as claimed in claim 6, characterized in that: In the step S3, the interface layer is cured by high-temperature rolling when the asphalt is coated, and both sides of the middle layer have a cured block copolymer interface layer, which is then combined with the asphalt coating.
8. A self-adhesive SBS modified asphalt waterproofing membrane as claimed in claim 7, characterized in that: The high modulus SBS modified asphalt ratio: Asphalt matrix 80%-85%, SBS modifier 10%-14% and tackifier 3%-5%, Low modulus SBS modified asphalt ratio: Asphalt matrix 85%-90%, SBS modifier 5%-8%, toughening agent coumarone resin, 3%-5%.
9. A self-adhesive SBS modified asphalt waterproofing membrane as claimed in claim 8, characterized in that: The method of performing anti-ultraviolet and antibacterial coating is: An automatic sprayer is used to spray anti-ultraviolet coating on the outer surface of the roll at a spraying pressure of 0.3-0.5MPa with a spraying thickness of 30-50μm. After the anti-ultraviolet layer is naturally air-dried for 15-20 minutes, antibacterial coating is sprayed with a spraying thickness of 40-60μm to form a surface protection layer to obtain a self-adhesive SBS modified asphalt waterproof roll.
10. A self-adhesive SBS modified asphalt waterproofing membrane as claimed in claim 9, characterized in that: The structural order of the waterproof membrane is: Center layer base, High modulus bituminous coating, Block copolymer interfacial layer, The middle layer of the tire base, Block copolymer interfacial layer, Low modulus bituminous coating, Outer tire base, UV resistant and antibacterial surface coating.
Citation Information
Patent Citations
Self-adhesion modified asphalt waterproofing coil coating material, preparation method thereof and passive special self-adhesion asphalt waterproofing coil for buildings
CN110746930A